A Review on the Persian Translation of “Drawings Archaeological Finds” - Mozhgan Jayez (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Drawing archaeological finds is one which stands out among the other means of documentation and information transfer in archaeological science. A wide range of objects is drawn during archeological activities. The present paper criticizes the translation of a book on the drawing of archeological objects. The main book in the original language is outdated, but it is a relatively reliable source. Considering that this book was regarded as one of the most important sources of drawing even before translation, its translation into Persian doubles its importance to Iranian archaeologists. The translated version of the book, which is published in Iran, suffers from the literal translation, unfamiliar and unusual equivalents, and low quality of the printed images, which play a major role in increasing the readers’ understanding of the content of the book. It should be considered that mastering the English language and having extended knowledge of the wide range of objects and archaeological finds are necessary for the translation of sourcebooks.